Abnormal differentiation of thymocytes induced by free cyclosporine is avoided when cyclosporine bound to N-(2-hydroxypropyl)methacrylamide copolymer carrier is used - St'astný, M; Ulbrich, K; Strohalm, J; Rossmann, P; Ríhová, B (Transplantation, 1997)
BACKGROUND: The side effects of cyclosporine (CsA)-including nephrotoxicity and abnormal differentiation of thymocytes developing in the thymus-can be decreased or even avoided using targeted conjugates of CsA, where both targeting moiety and drug are bound to water-soluble polymeric carrier based on N-(2-hydroxypropyl) methacrylamide (HPMA). METHODS: Irradiated, syngeneic bone marrow transplanted-mice (BALB/c and A/Ph) were treated intraperitoneally for 4 weeks with 20 mg/kg of free CsA, HPMA-conjugated CsA, or antibody-targeted HPMA-bound CsA. Immunohistology of the thymus was performed together with two-color flow cytometry to detect the effect of different forms of CsA on individual thymocyte subpopulations. RESULTS: . We have shown that free CsA strongly abrogated T-cell development. The appearance of mature thymocytes expressing CD3(high) is almost completely inhibited (1.8%) after free CsA treatment, whereas these cells are well detectable in controls (22%) and HPMA polymer-bound CsA-treated animals (19%). Immunohistological studies have shown acellular rests of the medulla after free CsA treatment, whereas well-stained medullary thymocytes were detected in controls and after exposure to antibody-targeted HPMA. conjugated CsA. CONCLUSIONS: HPMA-conjugates of CsA are generally more specific in their targeting to T lymphocytes. It was found that nonspecific binding of CsA to erythrocytes and plasma lipoproteins is significantly reduced using anti-CD3 targeted, HPMA polymer-bound CsA In addition, the entry of these macromolecules into the thymus is limited-probably due to the blood-thymus barrier-and HPMA conjugates of CsA, unlike free drug, do not abrogate T-cell development in bone marrow transplanted mice.
Keywords: cyklosporin; Immunosuppressive Agents; Rats; Mice, Inbred BALB C; Cell Differentiation; akrylamidy; Cyclosporine; Lipoproteins; mužské pohlaví; lipoproteiny; Mice; lékové transportní systémy; krysa rodu Rattus; Acrylamides; Concanavalin A; Polymers; CD8-pozitivní T-lymfocyty; Erythrocytes; ženské pohlaví; zvířata; erytrocyty; imunosupresiva; myši inbrední BALB C; Bone Marrow Transplantation; Thymus Gland; myši; transplantace kostní dřeně; buněčná diferenciace; CD4-pozitivní T-lymfocyty; Drug Delivery Systems; thymus; polymery; CD8-Positive T-Lymphocytes; Female; konkanavalin A; CD4-Positive T-Lymphocytes; Male; Animals